An investigation into the preparation and characteristics of carbonized rice straw for black food dye - Erni Sofia Murtini; Hendrix Yulis Setyawan; Sudarminto Setyo Yuwono; Luluk Mamluhah; Lisa Fitri Rahayu; Mingming Zhu; Chiemeka Onyeka Okoye (Cogent Food & Agriculture)
Traditional natural dye sources have limitations in terms of variability and availability. This study investigate explored rice straw as a sustainable food dyes, focusing on carbonised rice straw (CRS). The aim was to reduce the CRS silica content to meet the regulatory standards without compromising the dye quality. Various treatments with Sonication, HCl, NaOH, and pressurised NaOH effectively reduced silica to 0.96%, accompanied by increased sodium content. Optimisation of the NaOH concentration seeks to balance the silica reduction and sodium levels. Additionally, the impact of sonication on CRS particle size was assessed to enhance dye stability. The results showed that sonication effectively reduced CRS particle size, with longer durations and higher amplitudes leading to smaller particles and decreased sedimentation rates, indicating enhanced suspension stability. Optimised sonication conditions produced a liquid dye with desirable traits, including uniform particle distribution and minimal sedimentation at 9.0%. This study highlights the potential of rice straw as a sustainable and cost-effective alternative for black food dye production. By refining silica reduction and sonication processing techniques, CRS-derived black food dyes can meet quality standards, reduce agricultural waste, and support sustainable food production.